New dentognathic fossils of Noropithecus bulukensis (Primates, Victoriapithecidae) from the late Early Miocene of Buluk, Kenya. Issue 148 (November 2020) - Locke, Ellis M.; Benefit, Brenda R.; Kimock, Clare M.; Miller, Ellen R.; Nengo, Isaiah
Abstract: The late Early Miocene site of Buluk, Kenya, has yielded fossil remains of several catarrhine primates, including 16 dentognathic specimens of the stem cercopithecoid Noropithecus bulukensis . With the exception of the large sample of Victoriapithecus macinnesi from the middle Miocene of Maboko Island, Kenya, the majority of stem cercopithecoid taxa are represented by small sample sizes. We describe and analyze 91 new cercopithecoid fossils collected from Buluk between 2004 and 2018, including several previously undescribed tooth positions for N. bulukensis, and provide the first evaluation of dental metric and morphological variation in this sample. The results show that the expanded Buluk sample exhibits high levels of dental variation in the postcanine tooth row, similar to V. macinnesi at Maboko, but this variation is consistent with a single-species hypothesis. Subtle differences in the shape of the I 1, breadth of the C 1 and P 3, relative breadth of M 1, upper and lower molar distal shelf lengths, the degree of M2 basal flare, and a less-developed lower molar distal lophid differentiate the dentition of N. bulukensis from V. macinnesi . Although differences exist between the N. bulukensis and V. macinnesi dental samples, the high degree of variation within each sample complicates the identification of many individual specimens. New partial maxillae and mandibles allow reassessment of previously described diagnostic differences between N. bulukensis and V. macinnesi, negating upper molar arcade shape as a diagnostic feature and confirming the existence of differences in mandibular symphyseal morphology. Overall, new fossils from Buluk provide new evidence of the dentognathic anatomy of a medium-sized cercopithecoid that coexisted with a diverse group of noncercopithecoid catarrhines at the end of the early Miocene.